ANALISIS PERILAKU EKONOMI WANITA PEKERJA PADA GUDANG TEMBAKAU (Studi Kasus di Kabupaten Jember) - Yani Dahliani (STIE Mandala Jember, 2012)
The research aim to know that :(1)Why the women choose to work in tobaccostorage?(2)Are there influences the women worker in tobacco storage up to incomefamily?(3)Are there influences the women worker in tobacco storage to role domestichousehold?Research methode used was spread questioner to 6 storage tobacco in Jember. Every tobacco storage average 200-250 worker, that the big paft is women worker ,the methode put 1 0% responden to every tobacco storage also interview to responden. Resu/f this research that:(1)The women worker choosed to move from her village go to work to area tobacco industry, it because want to increase her income family, theyasumstion work in tobacco storage the have to get more money.(2)The women worker to have increase lncome for her family.(3)And The women worker in tobacca storage decrease role in her household.